Beyond hummus and falafel : social and political aspects of Palestinian food in Israel - Gvion, Liora (California studies in food and culture, 2012)
Beyond Hummus and Falafel is the story of how food has come to play a central role in how Palestinian citizens of Israel negotiate life and a shared cultural identity within a tense political context. At the household level, Palestinian women govern food culture in the home, replicating tradition and acting as agents of change and modernization, carefully adopting and adapting mainstream Jewish culinary practices and technologies in the kitchen. Food is at the center of how Arab culture minorities define and shape the boundaries and substance of their identity within Israel.